Relativistic Transitions in the Hydrogenic Atoms (Elementary Theory) - Boudet, R. (Springer, 2017)
Part I The Solutions of the Dirac Equation in Hydrogenic Atoms. Part II Fields Created by the Dirac Transition Currents Between Two States. Part III Interaction with Radiation. Part IV The Photoeffect. Part V Interaction with a Magnetic Field. Part VI Addendum. Part VII Appendices.